(untitled) (Nordic Journal of African Studies, 2011)
/ʌ/ is a vowel phoneme of kpɔ̍kɷ̀gbɷ̀, a Kru variety of Côte d’Ivoire. This segment has a fairly wide distribution and is a common vowel in this language. It is entirely integrated into the languages’ system of vowel harmony. At the same time, in stark contrast to the other 11 vowels of this variety, /ʌ/ shows a remarkable variation including transformations of /ʌ/ to [a] or [ɛ]. This occurs when /ʌ/ appears in specific prosodic environments. The change in vowel quality occurs under the influence of a tone modulation. Following a theoretical approach proposed by Kaye, Lowenstamm and Vergnaud (1985), /ʌ/ is analysed as a constituted by the elements v° an A+, with v° as head. Given that v° is an element without the feature ‘hot’, it does not obstruct complex tonal effects on /ʌ/, of which it is the head in the matrix structure. Résumé /ʌ/ est un phonème vocalique du kpɔ̍kɷ̀gbɷ̀, parler kru de Côte d’Ivoire. Ce segment n’a pas une distribution lacunaire et n’est pas la voyelle la moins productive de la langue. En outre, elle participe entièrement au fonctionnement des harmonies vocaliques en vigueur dans ce parler. Cependant, contrairement aux onze autres voyelles, /ʌ/ présente une variation remarquable. Elle consiste dans la transformation de /ʌ/ en [a] ou en [ɛ]. Cela se produit lorsque /ʌ/ est confrontée à certains phénomènes prosodiques. Cette voyelle se transforme surtout lorsqu’elle doit supporter une modulation tonale. Sa structure élémentaire est à la base de cette variabilité. En effet, /ʌ/ est formé des éléments v° et A+, avec v° comme tête. Or v° est un élément qui n’a pas de trait chaud. De ce fait, il ne peut résister à toute complexification tonale qui affecte le segment /ʌ/ dont il est la tête de la structure matricielle.